SOCIAL ECONOMIC LAW REFORM: LESSONS FROM DIFFERENT COUNTRIES BASED ON A LITERATURE REVIEW - Loso Judijanto (CV. Adiba Aisha Amira, 2024)
Social economic law reform is an important process undertaken by many countries to improve people's welfare and realise sustainable development. Literature from various countries shows that the success of social economy law reform depends on a holistic, participatory and adaptive approach, as well as the importance of transparency, accountability and effective law enforcement. In addition, law reform must be dynamic and responsive to change, with flexible and innovative approaches to law making and implementation. Cooperation between the government, private sector and civil society is also needed to create a more just, inclusive and prosperous society.